PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KPPN MERAUKE - WIDIARIAN, NEDDIAR (Jurnal Ilmu Manajemen (JIM), 2017)
The organization is growing and developing very dynamically, there is the easy changes occur that require an agency to adjustment and can accommodate any changes in the precise, fast, and effective. An organization or institution should be able to manage its resources, including manusisa resources (HR) is the main asset of great influence on the progress of the organization. As is known so far, more organizations deal with issues related to human resources when compared to other economic resources because it can not be equated with machines, materials and funds technical nature. This study aims to determine how much influence the stress of work and the work environment on employee performance at kantor pelayanan perbendaharaan negara merauke. This type of research is quantitative. The sampling technique is the whole population (sampling universe) portion of production is to sample 69 respondents. The statistical analysis used in this research is by using SPSS ( Statistics Programme for Social System) version 20. The scale of measurement in this study using a Likert scale. The results showed that the work stress negatively affect the performance of the production employees indicated by the t value of work stress 0.776. Meanwhile, work environment positive effect on the performance of the production employees with work environment t value 0.004. Interaction stress of work and the work environment influence simultaneously on employee performance with value f counted 0,000 Keywords: Work Stress, Work Environment and Employee, Performance